Sex of Household Heads and Attitude Towards Home Gardening in Southwest, Nigeria - Abdulrazaq Kamal DAUDU; Sidiqat Adeyemi Aderinoye-Abdulwahab (Journal of Agricultural Extension)
This study investigates gender differences and household attitude towards home garden in urban Nigeria. We used a cross-sectional sex-disaggregated survey data collected from a random sample of 480 households. We used attitudinal scale to measure household attitude towards the importance and benefits of home garden by gender and teacher made test to categorize their knowledge level of home garden. Both descriptive and inferential statistics were employed for data analysis. Results show that male households generally hold a more positive attitude towards home gardening compared to their female counterparts in the study area. Findings highlight a significant difference between male and female households in their levels of knowledge about home gardening, with females exhibiting higher levels of knowledge compared to males. Major constraints reported by households in home garden production include damage from pests, diseases, animals, and theft (male: 1.98±0.63; female: 1.96±0.61) and limited access to agricultural inputs such as seeds, tools, and capital (male: (1.94±0.77; female: 2.00±0.75). Tackling these identified constraints could contribute to improving household perceptions of home gardening, reducing gender disparities in attitudes, and enhancing food security outcomes.